DAMPAK MIGRASI TERHADAP KONDISI SOSIAL EKONOMI PENDUDUK SEBAGAI PEKERJA MIGRAN INDONESIA - Soinbala, Yerahmeel; Samin, Mikael; H. N. Mari, Natalia Adel (Jurnal Geografi, 2022)
This study aims to: (1) Determine the factors driving the villagers of Nunkolo to choose migration abroad (2) Examine the impact of migration village Nunkolo the socioeconomic conditions in the village Nunkolo District of Nunkolo South Central Timor. The research was conducted in Nunkolo Village, Nunkolo District, South Central Timor Regency using qualitative research methods. Data collection techniques using interviews, documentation, and triangulation using several stages of analysis and qualitative, namely data collection, data reduction, data presentation, and concluding. The results of this study indicate that the push and pull factors of a person choosing to migrate abroad as Indonesian migrant workers are due to information from previous PMIs, limited living needs in the area of ​​origin, lack of employment opportunities in the area of ​​origin, ease of job opportunities in the destination area and the size of the workforce. wages in the destination area. The existence of migration that occurred in Nunkolo Village, Nunkolo Sub-district, had a socio-economic impact in the form of the condition of the house being owned, which was the house itself with the physical condition of the permanent building. Meanwhile, the education level of children from ex-migrant families is only limited to secondary education or equivalent to high school. The type of work of former migrants after returning to their area of ​​origin is in the form of medium and low category jobs. The income earned by former migrants after migrating has increased compared to before. Family expenses also increased for food consumption such as rice, vegetables, tea, coffee, sugar, oil, kitchen spices, and others, while expenses for non-food consumption such as electricity, transportation, and paying for children's education.